Schistosomiasis Vector Snails and Their Microbiota Display a Phylosymbiosis Pattern - Huot, Camille; Clerissi, Camille; Gourbal, Benjamin; Galinier, Richard; Duval, David; Toulza, Eve (Frontiers in Microbiology, 2020)
Planorbidae snails are the intermediate host for the trematode parasite of the Schistosoma genus, which is responsible for schistosomiasis, a disease that affects both humans and cattle. The microbiota for Schistosoma has already been described as having an effect on host/parasite interactions, specifically through immunological interactions. Here, we sought to characterize the microbiota composition of seven Planorbidae species and strains. Individual snail microbiota was determined using 16S ribosomal DNA amplicon sequencing. The bacterial composition was highly specific to the host strain with limited interindividual variation. In addition, it displayed complete congruence with host phylogeny, revealing a phylosymbiosis pattern. These results were confirmed in a common garden, suggesting that the host highly constrains microbial composition. This study presents the first comparison of bacterial communities between several intermediate snail hosts of Schistosoma parasites, paving the way for further studies on the understanding of this tripartite interaction.